Contagion effects of the US subprime crisis in developed countries - Horta, Paulo (2012)
This study assesses whether capital markets of developed countries reflect the effects of financial contagion from the US subprime crisis and, in such case, if the intensity of contagion differs across countries. Adopting a definition of contagion that relates the phenomenon to an increase of cross-market linkages following a shock, copula models are used to analyse how the connections between the US and each market in the sample, evolved from the pre-crisis to the crisis period. The results suggest that markets in Canada, Japan, Italy, France and the United Kingdom display significant levels of contagion, which are less relevant in Germany. Canada appears to be the country where the highest intensity of contagion is observed.